2013
DOI: 10.12785/ijcnt/010202
|View full text |Cite
|
Sign up to set email alerts
|

Network Attack Analysis and the Behaviour Engine

Abstract: Behaviour Engines allow the acquisition of tacit knowledge by using a learn-by-doing workflow and provide a direct interface between the expert user and the developing project code based on an intuitive justification-conclusion language; thus surpassing legacy policy engines by being a self developing and learning mechanism. This paper seeks to formulate the current state of the art in technology and processes and attempts to merge the application of ontological decision techniques of behaviour engines with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In our review, we observed that quite a large number of countermeasures are either not evaluated at all ( [23], [40], [45] , [48] , [49] , [62] , [75] , [88] , [91] , [67] , [92] , [105] , [110], [111], [114], [137], [141], [154], , [160], [174], , [175]) or evaluated weakly ( [60], [70], [100], [109], [132], [138], [147], [158], [161], [165], [171]). We consider an evaluation as weak evaluation when the system is evaluated with a small dataset (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our review, we observed that quite a large number of countermeasures are either not evaluated at all ( [23], [40], [45] , [48] , [49] , [62] , [75] , [88] , [91] , [67] , [92] , [105] , [110], [111], [114], [137], [141], [154], , [160], [174], , [175]) or evaluated weakly ( [60], [70], [100], [109], [132], [138], [147], [158], [161], [165], [171]). We consider an evaluation as weak evaluation when the system is evaluated with a small dataset (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural approach seems a rich area for exploration, however, it should be noted that not all abnormal traffic will be data exfiltration. Benham et al [137] also advocate a behavioural approach to network modelling for data exfiltration, but one which is less sensitive to legitimate anomalies. They suggest a 'Behaviour Engine', which begins with no rules at all and gradually learns them by observing and querying a user's use of a network.…”
Section: Unsupervised Modementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have only mentioned those classifiers that were selected as best classifiers for a study because most of the studies initially tried out multiple classifiers. Considering the reflections from learning type, we classified the classifier structure into four types: base, Amnesia testbed dataset [125] , SQLMAP [126] [S59, S62, S70] Malware/RAT ESET NOD32 [127], Kingsoft [128], Anubis [129], VirusTotal [130], [S1, S41] APT Sysmon Tool [131], Winlogbeat [132] [S79] Overt Channels ZeuS Tracker [133], Waledac [134], Storm [135] [S22, S39] Side Channel PAPI [136] [S8, S63] Steganography F5 [137], Model Based Steganography [138], Outguess [139], YASS [140] [S3, S9, S20] Data dns2tcp [141],BRO [142],Iodine [143], dnscat [144] and Ozymandns [145], [S4, S14, S15, S21, Tunnelling CobaltStrike [146], ReverseDNShell [147] S29, S32, S67, S68,S80] Fig. 10: Analysis of ML Modelling Phase (The number shows the total studies in each category, while the bold number shows total studies in terms of y-axis) that can handle linear, non-linear, high dimensional data [154].…”
Section: Sql Injectionmentioning
confidence: 99%